The Effectiveness of Online Learning Based on Learning Outcomes in the Mathematics Course during the Covid-19 Pandemic Period - Farida Tuahuns; Fitri Savitri; Alifa Sabrina (Jurnal Pendidikan Matematika, 2022)
The implementation of online learning due to the COVID-19 pandemic by the Indonesian government through the Ministry of Education has led to changes in the condition of the lecture system in public and private universities. This study aimed to determine the effectiveness of online learning in the mathematics course at STIKes IKIFA in the Pharmacy Study Program during the 2020/2021 academic year using a quantitative descriptive method. Student learning outcomes from pretest and posttest were compared to find the differences before and after treatment during online learning. A total of 95 students were recruited as sample through total sampling. The measurement of the effectiveness of online learning based on students’ outcomes showed that 92.7% of students scored higher than 70 for posttest. The online learning would be considered effective if the students’ learning outcomes exceeded 80%. The effectiveness could also be seen in the increases in learning outcomes recorded by 85.26% of the students. It can be concluded that the online learning implemented in STIKes IKIFA was in the effective category. This result was made possible by a sound collaboration between the university and the lecturer as facilitator in creating an environment for online learning during the COVID-19 pandemic.